The tadpole of the Melville Range Treefrog Litoria andiirrmalin (Anura: Hylidae) - Meyer, Edward A.; Hines, Harry B.; Hoskin, Conrad J.; Mcdonald, Keith R. (Zootaxa, 2013)
The Melville Range Treefrog (Litoria andiirrmalin McDonald) is a large saxicolous hylid frog restricted to boulder-field streams of Cape Melville, northeast Australia (McDonald 1997). Due to difficulties accessing its remote habitat, the breeding biology of this highly distinctive species remains poorly known. Information on the morphology and habitat of larval L. andiirrmalin is provided below.